2020
DOI: 10.1007/jhep08(2020)163
|View full text |Cite
|
Sign up to set email alerts
|

A Lorentzian inversion formula for defect CFT

Abstract: We present a Lorentzian inversion formula valid for any defect CFT that extracts the bulk channel CFT data as an analytic function of the spin variable. This result complements the already obtained inversion formula for the corresponding defect channel, and makes it now possible to implement the analytic bootstrap program for defect CFT, by going back and forth between bulk and defect expansions. A crucial role in our derivation is played by the Calogero-Sutherland description of defect blocks which we review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 63 publications
(145 reference statements)
5
65
0
Order By: Relevance
“…The philosophy of the defect bootstrap is to explore the consistency conditions that follow from the associativity of the three operator expansions given above. In recent years there has been significant progress on this programme [7][8][9][10][11][12][13][14][15][16][17]. Just as in the ordinary (bulk) conformal bootstrap, it is essential to know the relevant conformal blocks which group the contributions of an entire conformal representation.…”
Section: Jhep01(2021)060mentioning
confidence: 99%
“…The philosophy of the defect bootstrap is to explore the consistency conditions that follow from the associativity of the three operator expansions given above. In recent years there has been significant progress on this programme [7][8][9][10][11][12][13][14][15][16][17]. Just as in the ordinary (bulk) conformal bootstrap, it is essential to know the relevant conformal blocks which group the contributions of an entire conformal representation.…”
Section: Jhep01(2021)060mentioning
confidence: 99%
“…correlation functions that involve one or more non-local operators like line or surface defects etc. Once again, the Calogero-Sutherland models for the relevant wave functions ψ are known from [30], at least in the scalar case. From this work on may also infer the analogue of the factorΩ.…”
Section: Jhep10(2020)004 6 Conclusion and Outlookmentioning
confidence: 99%
“…In the spinning case, one must additionally account for the Jacobian matrix ∂y a /∂x m . 5 Next we use conformal symmetry to express the correlator in terms of two vectors. This is similar to expressing the correlator in terms of two scalar cross-ratios, with the difference that here we fix two, instead of the customary three, positions using translations and special conformal transformations to express the correlator in terms of the remaining two position vectors.…”
Section: Regge Limitmentioning
confidence: 99%
“…In recent years it has been shown that powerful analytical results for scattering amplitudes in quantum field theory, namely the Froissart-Gribov formula and dispersion relations, have equally powerful CFT analogues in the Lorentzian inversion formula [1][2][3][4][5] and the two-variable CFT dispersion relation [6,7]. Dispersion relations reconstruct a scattering amplitude from the discontinuity of the amplitude, while the Froissart-Gribov formula extracts the partial wave coefficients from the discontinuity and makes their analyticity in spin manifest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation